Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Collectif LGBTQ* du Manitoba, 2023)
Comment pallier le risque accru de discrimination ou de stigmatisation auquel font face les membres de la Communauté dans leurs recours aux services ou dans leur participation aux événements, surtout en collaboration avec des organismes non francophones ou non 2ELGBTQ+ ? En quoi consistent concrètement l’accessibilité, l’inclusion et les pratiques prometteuses concernant l’offre de services sociaux et de santé destinés aux membres de la Communauté? Et selon quels critères objectifs établir des partenariats, concevoir des services ou encore évaluer et améliorer des services existants? Le présent projet a visé à répondre à ces questions, par le biais d’un nouvel outil de diagnostic. Le présent rapport présente premièrement la démarche qui a été entreprise pour développer cet outil de diagnostic. Il présente ensuite l’outil tel qu’il s’applique aux trois volets (santé, épanouissement social et culturel, éducation). Nous passons ensuite en revue les limites du projet actuel et proposons des recommandations pour les suivis à entreprendre. Ce rapport sert donc à la fois d’outil analytique à l’état d’essai et de plan d’action pour le Collectif afin de poursuivre la mise en œuvre des recommandations du rapport « Des nôtres »

Care Trajectories for Yukon Francophone Seniors - De Moissac, Danielle (Parteneriat communauté en santé, 2023)
Over the past several years, the Yukon Government has been exploring the matter of aging in place for its senior citizens (Government of Yukon, 2019). In the 2018 report entitled Yukon Health Status Report – Focus on Seniors, the Government of Yukon (2018) presented a profile of the health and well-being of Yukon seniors. t is important to note, however, that the voice of Francophone seniors is neither represented in the Focus on Seniors report (Government of Yukon, 2018) nor in the public engagement documentation, except for the mention of a liaison service for Francophones when discharged from the hospital (Government of Yukon, 2018 What we Heard About Aging in Place., p. 26). Although Francophones were able to participate in the engagement process, no mention was made about any specific needs of Francophone seniors. In light of the fact that Francophone seniors living in a minority language situation are aging at a proportionally faster rate than the overall Canadian population (Bouchard et al., 2015) and that this results in increased use of home care and other services (Van Kemenade, Bouchard & Bergeron, 2015), the needs of seniors from both of Yukon’s official language groups must be considered. This report provides information to further our understanding of this matter. Report Objectives: 1) To present findings related to Yukon Francophone senior care trajectories, from the moment when they first perceive the need for support with their overall health, on the physical as well as the mental and social levels. 2) To identify the care, health, and social service needs of these seniors, according to the services available, such that the active offer of French language services meets their needs.

Trajectoires de soins pour les aîné(e)es francophones du Yukon - de Moissac, Danielle (Partenariat communauté en santé, 2023)
Le gouvernement du Yukon s’intéresse depuis quelques années à la question du vieillissement chez soi pour sa population aînée (gouvernement du Yukon, 2019). Un rapport publié en 2018 intitulé Yukon Health Status Report: Focus on Seniors (Gouvernement du Yukon, 2018) présente le profil de santé et de mieux-être des aîné·e·s du territoire. Force est de constater, toutefois, que la voix des francophones n’est représentée ni dans le rapport sur la santé des aîné·e·s (Gouvernement du Yukon, 2018) ni dans les écrits émanant des consultations, autrement que par la mention d’un service de liaison pour les francophones à leur congé de l’hôpital (p. 26, Gouvernement du Yukon, 2018 What we Heard About Aging in Place.). Bien que des francophones aient pu participer aux consultations, aucune trace des besoins spécifiques des aîné·e·s de la francophonie n’est rapportée. Sachant que la population aînée francophone vivant en situation linguistique minoritaire vieillit proportionnellement plus rapidement que l’ensemble de la population canadienne (Bouchard et coll., 2015) et que cela engendre une utilisation accrue de soins à domicile et d’autres services (van Kemenade, Bouchard et Bergeron, 2015), il est important de saisir les besoins des personnes âgées issues des deux groupes de langues officielles du Yukon. Ce présent rapport pourra mieux nous informer à cet égard. Objectifs du rapport: 1) Exposer les constats relatifs aux trajectoires de soins pour les aîné·e·s francophones du Yukon, à partir du moment où ils ressentent le besoin de soutien en lien avec leur santé globale, tant physique que mentale et sociale; 2) Prendre connaissance des besoins de ces aîné·e·s quant aux soins et services sociaux et de santé, en relation avec les services disponibles dans une optique d’offre active de services en français qui répondent à leurs besoins.

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.